Thermo-Hydromechanical and Chemical Coupling in Geomaterials and Applications : Proceedings of the 3rd International Symposium GeoProc'2008 - Shao, Jian-Fu.; Burlion, Nicolas (London : Wiley, 2013)
GeoProc2008 collects the proceedings of the International Conference on Coupled T-H-M-C (thermal, hydraulic, mechanical, chemical) Processes in Geosystems.
Partially Coupled Fluid Flow Modeling for Stress Sensitive Naturally Fractured ReservoirsPoromechanical Modeling of Hygric Shrinkage and Crystallization Swellingin Layered Porous Materials; Fan-shaped Model of Clay Swelling Process; Early Age Autogenous Deformations of Cement-Based Materials; Identification of the Hydro-Mechanical in-Situ Properties of Tournemire Argillite from Mine-by-test Experiment; Model of Coupled Thermo-Hydraulic Transport in Bentonite Based on Mobile and Immobile Water Phase; Orthotropic Anisotropic Damage Coupled Modeling of Saturated Porous Rock.
Numerical Evaluation of Effective Transport Properties of Random Cell Models: Two-Point Probability Approach.
Print version record.
Keywords: Rock mechanics -- Mathematical models -- Congresses; Soil mechanics -- Mathematical models -- Congresses; Rock mechanics -- Mathematical models -- Congresses; Soil mechanics -- Mathematical models -- Congresses; Rock mechanics -- Mathematical models; Soil mechanics -- Mathematical models; Electronic books; Conference papers and proceedings